Acute Torsion of Appendicular Mucocele. (27th April 2017) - Ejtehadi, Farshid; Brooks, James; Ali, Hebah Hassan; Vijay, Vardhini
Abstract : We present the case of an 81-year-old man with a known appendicular mucocele who presented to the emergency department with acute abdominal pain. A CT scan showed a change in orientation of the previously seen ovoid mass with surrounding fat stranding suggesting torsion. An emergency laparotomy with appendicectomy and resection of the caecal pole was performed. We discuss the findings and histopathology.